Refractory metastatic colorectal cancer: challenges and solutions during the COVID-19 pandemic - Marina I. Sekacheva (IP Habib O.N., 2021)
Colorectal cancer (CRC) is one of the leading cancers in terms of prevalence and mortality. Almost 1/4 of patients with CRC have metastases at the initial presentation. The survival rate of this group of patients remains low. With the onset of the COVID-19 pandemic, cancer patients have faced difficulties in getting diagnosis or treatment, which could potentially lead to an increase in late-stage tumors and mortality. This situation required changes in approaches to the treatment of cancer patients, such as replacing drugs with tablet forms, schemes with long intervals, and much more. It is known that about 50% of patients with metastatic colorectal cancer survive in satisfactory condition until the 3rd line drug therapy or longer. One of the main drugs for this category of patients is regorafenib, which, thanks to the tablet formulation, has become especially important in the COVID-19 pandemic. In numerous clinical studies, the drug showed an increase in patient overall survival and good safety profile. In addition, there is growing evidence of the effect of regorafenib on tumor sensitivity to treatment with platinum drugs, irinotecan, and EGFR inhibitors.